A study of common Filipino terms and expressions as learned and used by Thai students in their daily interactions - Tongdee Keamarattrakun 1952-
This study attempted to answer the following: (1) the places of residence where Thai students in the Philippines stay and the influences these places have in their acquisition of Filipino; (2) the most well-known and most often used Filipino terms and expressions and from where they have learned them; (3) the language structure readily acquired; and (4) what prods the students to learn Filipino and what they feel about learning it. To arrive at the answers, the writer followed the following procedure: 1. making a list of Filipino terms and expressions 2. framing a questionnaire 3. distribution of the questionnaire to 196 Thai students enrolled in different universities in the Philippines 4. collection of the questionnaires through the presidents of the Thai Student Organization and 5. analysis and interpretation of the data. The data revealed that majority of the Thai students stay in apartments, a good portion in boarding houses, and a few in dormitories. Those who stay in apartments readily increase the number of words learned.